Radio frequency and coaxial cable assemblies. Detail specification for semi rigid cable assemblies (jumper). Frequency range up to 6000 MHz, type 50-9 semi-rigid coaxial cable Part 4-2, (31st August 2022) - British Standards Institution,
No abstract available